2022
DOI: 10.1021/acs.jpclett.2c01982
|View full text |Cite
|
Sign up to set email alerts
|

Patterning an Erosion-Free Polymeric Semiconductor Channel for Reliable All-Photolithography Organic Electronics

Abstract: Reliable patterning of organic semiconductors (OSCs) with high uniformity is essential to all-photolithography organic electronics. However, the majority of cross-linked OSCs experience performance fluctuations after photolithography because of the inherent vulnerability of low-ordered regions. Herein, we develop an anti-solution penetration photolithography process to achieve the reliable patterning of the OSC layer for allphotolithography integrated organic electronics. Using a thick and highly cross-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In 2022, it was further demonstrated that the all‐photolithography integrated organic electronics were based on SP‐1 system. [ 67 ] This effort conducted an investigation to understand the relationship between the degree of cross‐linking and the quality of the final film. They examined various factors such as the UV irradiation power, the developer (solvent used for the OSC film), and the film thickness.…”
Section: Lithography‐compatible Organic Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, it was further demonstrated that the all‐photolithography integrated organic electronics were based on SP‐1 system. [ 67 ] This effort conducted an investigation to understand the relationship between the degree of cross‐linking and the quality of the final film. They examined various factors such as the UV irradiation power, the developer (solvent used for the OSC film), and the film thickness.…”
Section: Lithography‐compatible Organic Semiconductorsmentioning
confidence: 99%
“…j) Output characteristics of 15-stage organic ring oscillators. Reproduced with permission [67]. Copyright 2022, American Chemical Society.…”
mentioning
confidence: 99%
“…The constructed logic gates correctly outputted the operation results that correspond to the truth table of each logic gate in Figure 3f for two input voltages (A and B). Chen et al demonstrated that it is possible to pattern organic semiconductors with a high yield by developing an anti-solution penetration photolithography process [55]. This was achieved using highly cross-linked semiconductor films to prevent the dissolution of the low-ordered region, and through delicate patterning they implemented a 15-state ring oscillator (Figure 3g,h).…”
Section: Organic-based Thin-film Digital Circuitsmentioning
confidence: 99%
“…Lithography is a crucial process for manufacturing electronic devices. Various lithographic processes, such as photolithography, [1,2] e-beam lithography, [3] and direct writing, [4] can form defined patterns on which the charge transport behavior is modulated according to the device applications, including field-effect transistors, [5,6] diodes, [7,8] photodetectors, [9,10] gas sensors, [11][12][13] and memory devices. [14,15] Tremendous effort has been made in lithography techniques to shrink and shorten pattern lengths since short-channel devices offer a lower power consumption and higher driving current.…”
Section: Introductionmentioning
confidence: 99%